PENGARUH PEOPLE DAN PHYSICAL EVIDENCE TERHADAP KEPUASAN PASIEN DI RSUD BIMA - Filansyah; Sri Ernawati (Universitas Mahendradatta, 2022)
This study aims to determine the effect of people and physical evidence partiallyand simultaneously on consumer satisfaction at Bima Hospital. Data was collected bydistributing questionnaires to 50 patients. Data analysis used validity test, reliability test,classical assumption, multiple linear regression, determination, correlation, t test and f testwith SPSS 23.0 application. The results of this study indicate that there is no significant effectof the people variable on consumer satisfaction at Bima Hospital, there is a significantinfluence of physical evidence on consumer satisfaction at Bima Hospital and there is asignificant influence of people and physical evidence on consumer satisfaction at BimaHospital.